A new genus of giant lacewing (Insecta, Neuroptera, Ithonidae) from the Middle Jurassic of China - Yang, Qiang; Shi, Chaofan; Pang, Hong; Ren, Dong (Zootaxa, 2019)
A new genus and species of Ithonidae, Puripolystoechotes pumilus gen. et sp. nov., is described from the Middle Jurassic of Inner Mongolia, China. The new genus is distinguished by possessing a hind wing with a simple humeral vein, only three ra-rp crossveins, M forked slightly distal to origin of RP1, and wing membrane without color pattern. This is the third ithonid genus from this locality, showing interesting morphological similarity with the other ithonids from the same locality and period.